Everything conceivable how assisted reproduction is changing men, women, and the world - Mundy, Liza 1960- (Alfred A. Knopf, 2007)
Skyrocketing infertility rates and the accompanying explosion in reproductive technology are revolutionizing the American family and changing the way we think about parenthood, childbirth, and life itself. In this work of investigative reporting, journalist Mundy captures the human narratives, as well as the science, behind what is today a controversial, multibillion-dollar industry, and examines how the huge social experiment that is assisted reproduction is transforming our most basic relationships and even our destiny as a species.--From publisher description.